Infertility In India: A Comprehensive Narrative Review Of Epidemiological, Psychosocial, And Genetic Risk Factors (2010–2024) - Yusupova Umida Masharifovna (International Journal of Medical Sciences And Clinical Research, 2025)
Background: Infertility, the inability to achieve conception after 12 months of regular unprotected intercourse, is a growing reproductive health concern in India. Despite being recognized as a public health issue with major psychosocial consequences, infertility remains under-researched and stigmatized. Global prevalence is estimated at 8–12%, yet Indian data vary regionally due to differences in healthcare access, social norms, and biological determinants. Objective: This narrative review synthesizes epidemiological, clinical, psychosocial, and molecular research on infertility in India from 2010–2024, highlighting prevalence patterns, regional variations, and key risk factors influencing reproductive outcomes. Methods: A narrative synthesis was conducted using eight major studies published between 2010 and 2024, encompassing community surveys, hospital-based cross-sectional analyses, and a genetic case–control investigation. Comparative interpretation focused on sociodemographic, reproductive, psychological, and genetic domains influencing primary and secondary infertility. Results: The prevalence of infertility in Indian populations ranged between 6% and 13%, consistent with WHO global estimates. Primary infertility predominated in younger, rural populations, while secondary infertility was more common among women with prior reproductive or infectious histories. Key determinants included age at marriage, menstrual irregularities, RTI/STI history, PCOD, socioeconomic status, and psychological stress. Genetic studies identified novel associations between VEGF promoter polymorphisms (−2578C/A, −2549I/D, −460T/C) and infertility risk in North-West Indians. Psychosocial research revealed infertility-specific stress in up to 80% of affected women. Conclusion: Infertility in India is multifactorial, reflecting complex interactions among biological, social, and genetic variables. Regional disparities persist, underscoring the need for holistic interventions integrating reproductive health services, mental health care, and molecular diagnostics.